Re-examination of the post half-time reduction in soccer work-rate - Lovell, R.; Barrett, S.; Portas, M.; Weston, M. (Journal of Science and Medicine in Sport, 2013)
Objectives: To re-examine the work-rate of soccer players immediately after a passive half-time interval with an alternative approach to data reduction and statistical contrasts. Design: Time-motion analysis data (5 Hz global positioning system), were collected from 20 elite youth players (age: 17 ± 1 years) during 21 competitive league fixtures (5 ± 3 matches per player). Methods: Physical performances were categorised into total distance covered, total low-speed running (0-14.9 km h-1) and total high-speed running (15.0-35.0 km h-1). These dependent variables were subsequently time averaged into pre-determined periods of 5-, 15- and 45-min duration, and expressed in relative (m min-1) terms to allow direct comparisons between match periods of different lengths. During the 15-min half-time interval players were passive (seated rest). Results: There was a large reduction in relative total distance covered (effect size - standardised mean difference - 1.85), low-speed running (effect size -1.74) and high-speed running (effect size -1.37) during the opening 5-min phase of the second half (46-50 min) when compared to the first half mean (0-45 min). When comparing the 51-55 and 56-60-min periods, effect sizes were trivial for relative total distance covered (effect size -0.13; -0.04), low-speed running (effect size -0.10; -0.11) and small/trivial for high-speed running (-0.39; 0.11). Conclusions: Using a more robust analytical approach, the findings of this study support and extend previous research demonstrating that players work-rate was markedly lower in the first 5-min after a passive half-time interval, although we observed this phenomenon to be transient in nature. Time-motion analysts might re-consider their data reduction methods and comparators to distinguish within-match player work-rate trends.